2015
DOI: 10.4097/kjae.2015.68.4.411
|View full text |Cite
|
Sign up to set email alerts
|

The use of lung ultrasonography to confirm lung isolation in an infant who underwent emergent video-assisted thoracoscopic surgery: a case report

Abstract: Video-assisted thoracoscopic surgery for pediatric patients has gained popularity due to better outcomes than open surgery. For this procedure, one-lung ventilation may be necessary to provide an adequate surgical field. Confirming lung isolation is crucial when one-lung ventilation is required. Recently, we experienced a case in which one-lung ventilation was confirmed by ultrasonography using the lung sliding sign and the lung pulse in an infant. Since lung ultrasonography can be performed easily and quickly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Although the accuracy of LUS also decreased (85% in the previous study vs. 70.5% in the present study), it is still significantly higher than that of auscultation. Nam et al [13] reported the use of LUS to confirm lung isolation in an infant. Using LUS, the authors could achieve successful positioning of the endobronchial tube, when a skilled bronchoscopy operator was not available in the emergency setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although the accuracy of LUS also decreased (85% in the previous study vs. 70.5% in the present study), it is still significantly higher than that of auscultation. Nam et al [13] reported the use of LUS to confirm lung isolation in an infant. Using LUS, the authors could achieve successful positioning of the endobronchial tube, when a skilled bronchoscopy operator was not available in the emergency setting.…”
Section: Discussionmentioning
confidence: 99%
“…Nam JS ve ark. [20] TAV'a geçildiğinde gelişebilecek hipokseminin ve hava yolu basınç artışının özellikle pediatrik hastalarda daha riskli olabileceğini bildirdi. Pediatrik hastaların desatürasyona daha duyarlı olmaları nedeniyle FOB ile ÇLT pozisyonu doğrulanırken oluşabilecek hipokseminin mortal olabileceğini ve USG ile doğrulama yönteminin pediatrik hastalarda kullanımının daha yaygınlaşabileceğini bildirmişlerdir.…”
Section: Discussionunclassified
“…In addition, lung ultrasonography can be useful to evaluate diaphragm function, although there is no consensus on the sensitivity of ultrasound in this assessment. 10…”
Section: Discussionmentioning
confidence: 99%